Photography by Massinissa Garaoun | Linguistic fieldwork in North Africa | Traditionals pottery (gargoulette) and weaving (blankets) Aït Bouycef - (:unkn) unknown (My University, 2023)
This photograph has been captured by Massinissa Garaoun, and show a traditional pottery (gargoulette) and weaving (blankets) of the Aït Bouycef.This was part of a linguistic survey to document Tasahlit [θasaħliθ], a Berber language spoken by approximately 200 000 speakers in the western third of the Babor Range in Eastern Kabylia (Algeria).
Keywords: African Research